2019
DOI: 10.1186/s12885-019-5353-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts induce epithelial–mesenchymal transition of bladder cancer cells through paracrine IL-6 signalling

Abstract: BackgroundCancer-associated fibroblasts (CAFs), activated by tumour cells, are the predominant type of stromal cells in cancer tissue and play an important role in interacting with neoplastic cells to promote cancer progression. Epithelial-mesenchymal transition (EMT) is a key feature of metastatic cells. However, the mechanism by which CAFs induce EMT program in bladder cancer cells remains unclear.MethodsTo investigate the role of CAFs in bladder cancer progression, healthy primary bladder fibroblasts (HFs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(186 citation statements)
references
References 44 publications
(43 reference statements)
8
178
0
Order By: Relevance
“…for efficient SDF-1 and TGF-β crosstalk. Following the above data, CAF, as has been shown [104], can promote aggressive metastatic phenotypes of non-invasive bladder cancer cells through an EMT induced by the secretion of IL-6. A critical study [105] showed that CAFs induced invasion through a heterophilic adhesion to both the participating N-cadherin on the membranes of CAFs and the E cadherin on the membranes of the cancer cells.…”
Section: Circulating Cancer Cells Form Clusters Through Tomo-and Hetesupporting
confidence: 57%
“…for efficient SDF-1 and TGF-β crosstalk. Following the above data, CAF, as has been shown [104], can promote aggressive metastatic phenotypes of non-invasive bladder cancer cells through an EMT induced by the secretion of IL-6. A critical study [105] showed that CAFs induced invasion through a heterophilic adhesion to both the participating N-cadherin on the membranes of CAFs and the E cadherin on the membranes of the cancer cells.…”
Section: Circulating Cancer Cells Form Clusters Through Tomo-and Hetesupporting
confidence: 57%
“…The past years, stromal cells have been recognized as not only passive bystanders, but active key players in tumor progression 50 . While experimental functional studies have described tumor-supportive as well as tumor -restraining functions of CAFs in the UBC context, clinical evidence for the existence of different functional subsets remains sparse 5,[15][16][17]51 . The presented study has analyzed the interaction of the five stromal markers ASMA, CD90, FAP, PDGFRa and -b with survival and histopathological data within a UBC cohort.…”
Section: Discussionmentioning
confidence: 99%
“…experimental studies have demonstrated functional evidence for a modulatory role of fibroblasts on urothelial tumor cells in vitro and in vivo. While the majority of these studies describe pro-tumoral effects of fibroblasts derived growth-factors, like the induction of epithelial to mesenchymal transition and invasion 5,10,15,16 , one study also demonstrated that sonic hedgehog (Shh) activated fibroblasts exhibit rather tumor restraining functions during the transition of in situ to invasive UBC 17 . These findings, taken together with studies on fibroblast -tumor cell interactions in other solid tumors, point towards the existence of different fibroblast subsets with different functional roles at various stages of tumor progression and invasion (reviewed in [18][19][20][21][22][23] ).…”
mentioning
confidence: 99%
“…For example, Sun et al found that CAFs exosome promoted oral squamous cell carcinoma (OSCC) cell migration and invasion by transporting miR‐382‐5p to OSCC cells . A recent study demonstrated that activated CAFs can secrete interleukin‐6 (IL‐6) to promote epithelial mesenchymal transformation of BC cells and participate in the regulation of proliferation and migration of BC cells . These findings highlighted the important role of CAFs‐exosome in mediating cell‐to‐cell communication in regulating cancer development.…”
Section: Discussionmentioning
confidence: 99%